Determinant factors of anemia in pregnancy based on health belief model: a correlational study - Triharini, Mira; Eka Mishbahatul Mar'ah Has; Gita Nofita (Jurnal Ners, 2023)
Introduction: Pregnancy anemia is still a big problem worldwide. Health behavior can be influenced by perceptions of the importance of disease prevention. The theory of the Health Belief Model can study the relationship between prevention efforts and perceptions. The purpose was to analyze the relationship between perceived susceptibility, perceived severity, perceived benefit, perceived barrier, self-efficacy and cues to action with anemia prevention behaviors. Methods: This study used a correlational design cross-sectional approach. The total samples were 104 pregnant women selected using purposive sampling. The independent variables in this study were perceived susceptibility, perceived severity, perceived benefit, perceived barrier, self-efficacy, and cues to action. The dependent variable in this study was anemia prevention behaviors. Data were collected at one obstetrical polyclinic in hospital and also home visits were conducted to respondents who did not come to the hospital. The instrument used questionnaires on perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, cues to action and anemia prevention behaviors. Results: Perceived susceptibility (p=0.023 r=0.223), and cues to action (p=0.037 r=0.204) had a significant relationship with anemia prevention behaviors., while there was no relation between perceived severity (p= 0.839), perceived benefit (p= 0.986), perceived barrier (p= 0.585), and self-efficacy (p=0.399) with anemia prevention behaviors. Conclusions: Health workers can increase the susceptibility and cues to action of pregnant women through health education about anemia prevention.